Smithsonian book of national wildlife refuges / Eric Jay Dolin ; photographs by John and Karen Hollingsworth. - Dolin, Eric Jay. (Smithsonian Institution Press, 2003)
In 1903 Theodore Roosevelt signed a proclamation that created the first of what, a century later, would become a system of 538 wildlife refuges spread across all fifty of the United States. Stretching from the cypress swamps of Okefenokee to the remote wilderness of Alaska's Arctic National Wildlife Refuge, the refuges now occupy an amazing 95 million acres of the American landscape. These are America's most treasured natural habitats-filled with waterfowl, fish, mammals, and a diverse array of plants. Coupling his text with the remarkable photographs of John and Karen Hollingsworth, Eric Dolin draws on the rich history surrounding the refuges to reveal an intriguing story of people and nature. After exploring how the fledgling conservation movement found its champion in Teddy Roosevelt, Dolin unveils a story filled with heroic, sometimes quirky, Americans who fought to preserve the nation's natural heritage.